Eosinophilic gastroenteritis: A case report of a rare disease mimicking acute abdomen (Indian Journal of Case Reports, 2020)
Eosinophilic gastroenteritis (EGE) is a rare disease that can present as acute abdomen and can be challenging for a clinician to differentiate amidst the numerous causes of abdominal pain. Due to the non-specificity of symptoms and scarcity of diagnostic guidelines, a high index of suspicion is required to diagnose EGE and thereby defer unnecessary surgical interventions. Herein, we present the case of a 17-year-old female who had presented to the emergency department (ED) with severe abdominal pain and peripheral eosinophilia mimicking an acute abdomen. The relevance of the case resides in highlighting the fact that such rare diseases are often missed in ED and a broader diagnostic spectrum should be considered while evaluating cases of undifferentiated acute abdomen.